(untitled) (Ictus, 2021)
Editorial presented by Dr. Carlos Cantú-Brito Head of the Neurology Service of Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán, for volume 2 number 2 May 2021 of Ictus.